O caos é uma escada? uma aproximação entre a narrativa de Sansa Stark e a violência contra a mulher no Brasil - Lima, Gabriela (2023)
We know that violence against women is a global phenomenon that follows their history through time. Several works have sought to represent the many causes and consequences of behaviors that lead to this type of violence, such as the conception of male superiority, relationships of financial dependency, and differences in positions and salaries between men and women, among others. In A Song of Ice and Fire, a series of novels written by George R. R. Martin between 1996 and 2011, we find, throughout the story of the character Sansa Stark, some of those causes and consequences, which are still present in contemporary times, even though they are represented in a distant past (there is no mention of specific time in the series, but we suppose the time frames of the narrative indicate a medieval era). Therefore, in the light of women’s history, violence against women in Brazil and formulations about fantasy, this dissertation aims to analyze the construction of the character Sansa Stark in Martin’s As Crônicas de Gelo e Fogo, translated into Portuguese by Jorge Candeias and Márcia Blasques, between 2010 and 2012, while trying to highlight a parallel between her trajectory and that of many Brazilian women, with regard to situations of violence. In this way, we observe the themes that are configured in the text of the novels, such as the patterns established in women’s history by patriarchy, the fantasy elements and the inspiration in some historical facts that underpin the plot created by the author, and the types of violence experienced by the character aligned with the rates of violence against women in Brazil. In addition, we analyze the path to female empowerment of the character, which determined her survival in the saga. To support our research, we have used studies by Michelle Perrot (2005, 2019), Virginia Woolf (2019), Simone de Beauvoir (2019, v. 1; 2019, v. 2), and Pierre Bourdieu (2012), among others concerning women’s studies. About the history of Brazilian women victims of violence, we have presented a specific study based on critics such as Gilberto Freyre (2013), Maria Ângela D’Incao (2004), and Mary Del Priore (2011), among others. Finally, for the study of fantasy, authors, such as Tzvetan Todorov (2004), Kari Maund (2012), and David Roas (2014), were essential. With our research, we found that, in contemporary Brazilian society, violence against women is still very pronounced, even though laws and social behaviors have improved their active social participation. Therefore, we think that academic works that investigate relations of subjection and aggression against women is still relevant in different areas of knowledge.